Ultrasonography for rheumatic diseases – a review - HEMALATHA.R.J; DR.VIJAYABASKAR.V (International Journal of Pharma and Bio Sciences, 2017)
Radiograph is considered as the gold standard method for imaging Rheumatoid arthritis. However features and information of imaging of synovium, soft tissues, and joint spaces are difficult to assess. More recently due to the improvement in the imaging technology musculoskeletal ultrasonography is increasingly being used in the clinical evaluation of arthritis diseases. This article aims at addressing the wide practice of musculoskeletal ultrasound in assessing the RA disease and highlights the strength of the imaging modality. Specific emphasis is placed on the methodology, design, and parameters used in the trials. A literature review was performed based on the title - role of ultrasound in assessing RA. Articles that detailed the applications of ultrasound experimentally and clinically were reviewed and the studies that compared ultrasound with MRI, X-ray imaging techniques were also included in the literature. This review article describes the role of musculoskeletal ultrasonography in patients with RA, focusing on identifying specific ultrasonographic features like vascular synovitis, tenosynovitis, bone erosions which can be an added value in evaluation of patients with arthritis.